2005
DOI: 10.1021/bi047817f
|View full text |Cite
|
Sign up to set email alerts
|

Primary Contact Sites in Intrinsically Unstructured Proteins:  The Case of Calpastatin and Microtubule-Associated Protein 2

Abstract: Intrinsically unstructured proteins (IUPs) exist in a disordered conformational state, often considered to be equivalent with the random-coil structure. We challenge this simplifying view by limited proteolysis, circular dichroism (CD) spectroscopy, and solid-state (1)H NMR, to show short- and long-range structural organization in two IUPs, the first inhibitory domain of calpastatin (CSD1) and microtubule-associated protein 2c (MAP2c). Proteases of either narrow (trypsin, chymotrypsin, and plasmin) or broad (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 61 publications
10
106
0
1
Order By: Relevance
“…1b). It has been observed that many IDPs exhibit regions of residual structure, which are believed to function as primary interaction sites (14). In support of this hypothesis, our study indicates that two of the functional secondary structural elements of PDE␥ are partially formed in the uncomplexed protein.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1b). It has been observed that many IDPs exhibit regions of residual structure, which are believed to function as primary interaction sites (14). In support of this hypothesis, our study indicates that two of the functional secondary structural elements of PDE␥ are partially formed in the uncomplexed protein.…”
Section: Discussionsupporting
confidence: 84%
“…A surge of recent evidence has established that both denatured proteins and IDPs can contain residual structure and even adopt compact folds in solution (10)(11)(12)(13). The residual structure of an IDP is believed to play a role in initiating the folding process, in protein-protein interactions, or in preventing aggregation (10,14,15). Despite the great challenge to structure determination imposed by the dynamic properties of an IDP, recently developed NMR methods, such as paramagnetic relaxation enhancement (PRE) (16) and residual dipolar coupling (RDC) (17), have enabled detailed elucidation of their transient conformations.…”
mentioning
confidence: 99%
“…The 15 N-and 15 N-13 C-labeled protein was expressed similarly. The protein was initially purified as described previously [5], and then on a C-18 HPLC column: final purity >98%.…”
Section: Preparation Of Calpastatin Domainmentioning
confidence: 99%
“…Despite their lack of a globular structure, intrinsically disordered proteins play key roles in signal transduction and other critical cellular processes (59)(60)(61). Biochemical and biophysical characterizations of these unstructured proteins have revealed that residual structure, including permanent or transient secondary structural elements, can be present in these proteins and function as protein recognition motifs (62). Stabilization of the residual structure is often coupled with other activities: some unstructured proteins and peptides become folded upon binding to their biological targets (60,63,64); others are unfolded under aqueous conditions but fold in the presence of lipids or model membranes (65)(66)(67).…”
Section: Micelle-induced Ordering Of Tsp9mentioning
confidence: 99%
“…Thermodynamically, the induced-folding process is always accompanied by significant entropy-enthalpy compensation. It is believed that the physiological importance of the residual structure is to facilitate molecular recognition during protein-protein interaction (62), and the induced folding allows fine control over binding affinity (63). For TSP9, it is also possible that the micelle-induced folding controls its functional specificity in the thylakoid membrane.…”
Section: Micelle-induced Ordering Of Tsp9mentioning
confidence: 99%